Grazing during the grassland greenup period promotes plant species richness in alpine grassland in winter pastures - Wei, Wanrong; Zhen, Qiaoyan; Deng, Jia; Yue, Hanlin; Qin, Mingsen; Oosthuizen, Maria K. (Frontiers in Plant Science, 2022)
Although grazing is the most common use of grassland, the ecological function of grassland far exceeds its productivity. Therefore, the protection of plant diversity is of the utmost importance and cannot be ignored. Existing research on the effect of grazing on grassland mainly focuses on grazing intensity and the type of livestock, but the consequences of the timing of the grazing on the vegetation community remains unclear. We investigated plant community characteristics of winter pastures in alpine meadow with different grazing termination times (grazing before and during the grassland greenup periods) in Maqu County, eastern QTP. The results showed that vegetation height, coverage, aboveground biomass and Graminoid biomass were lower in grassland when grazing happened during the greenup period compared to grassland where grazing was terminated before the greenup period. However, the total plant species richness and forbs richness were higher in grassland with grazing during the greenup period compared to grassland without grazing during the greenup period. Our structural equation modeling reveals a potential indirect implication for the total plant species richness and forbs richness of winter pastures mainly through a decrease in the vegetation coverage and grass biomass abundance. Our findings imply that grazing during the grassland greenup period may facilitate the maintenance of plant diversity in winter pastures. These findings have important implications for grassland ecosystem functioning and for the conservation of plant diversity.